PERBANDINGAN EFEKTIVITAS MISOPROSTOL DOSIS 50 µg DAN 100 µg TERHADAP KEBERHASILAN KELAHIRAN INDUKSI DI RSU PKU MUHAMMADIYAH YOGYAKARTA - Haafizah Dania; Djoko Wahyono; Sulistiari Retnowati (Universitas Ahmad Dahlan, 2014)
In recent years, misoprostol that is a prostaglandin E1 analogue has been used in cervix ripeningat pregnancy and labor induction. However, until now misoprostol dosage and administration route forinduction are various. There is no fix guide on administration and dosage of misoprostol. This researchwas intended to identify profile of misoprostol usage and effectiveness of misoprostol administrationat dosage of 50 Âµg and 100 µg on labor process progress of patient hospitalized in Yogyakarta PKUMuhammadiyah Hospital based on induction success. This research was non experimental research with historical cohort design. Limitation of this method was not all desired data exist in medical recordand capability of physician was not same. Subject was pregnant mothers giving birth with misoprostolinduction process in delivery room in Yogyakarta PKU Muhammadiyah Hospital from 1 January 2009to 31 December 2010. Data was obtained from medical record, which was then analyzed descriptivelyanalytically to identify misoprostol usage profile and effectiveness of misoprostol tablet administrationat 50 µg and 100 µg dosage on labor process progress. Research subjects who meet the inclusioncriteria in this research was 109 mothers, where 69 women (63,30%) got 50 µg misoprostol and 40women (36,70%) got 100 µg misoprostol. The results of this study indicate that the success ofinduction at 50 ug misoprostol group decreased by 89% compared with 100 ug misoprostol group (RR= 0.11), where the success of 50 ug misoprostol induction for 56 people from 69 people (81.16%),while the success induction at 100 ug misoprostol group as many as 39 people from 40 people(97.50%). The difference was statistically significant with p = 0.014 (p <0.05).